Education on the Relationship between Body Mass Index and Balanced Nutrition for School-Age Children Through Video Learning (Case Study of Integrated Islamic Elementary School Daarul Fikri grade 6, Cihanjuang Village) - Zerlina Ghina Hanifah; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2022)
This study aims to determine the level of students' understanding through learning videos regarding the relationship between Body Mass Index (BMI) education and balanced nutrition in 6th grade elementary school-aged children at integrated Islamic elementary school Daarul Fikri, Cihanjuang Village. Quantitative research method with pre-experimental design type one group pretest-posttest. The research was conducted on 20 6th grade students of integrated Islamic elementary school Daarul Fikri. The research was conducted in 3 stages, namely (i) pre-test; (ii) education through learning videos; and (iii) post-test. The results showed the average value of the pretest was 67.25 and the average posttest was 79.25. The comparison of pretest and posttest showed an increase in students' knowledge after taking action through learning videos. The result of calculating the average N-Gain value is 0.34 (34%) which shows that education through learning videos regarding the relationship between Body Mass Index (BMI) and balanced nutrition is not effective. This is because the students' pre-test scores are quite good. As for the results of the calculation of the t-test, it is known that T count (-6.564) < T table (1.729) means that the posttest scores of students increase but are not significant. With the completion of this study, it is hoped that more school-age children will understand the relationship between Body Mass Index and balanced nutrition. That we can identify the nutritional status that will affect the health of our bodies.